Er,Yb:Ca3RE2(BO3)4 (RE=Y, Gd) – Novel 1.5 μm Laser Crystals - K. N. Gorbachenya; R. V. Deineka; V. E. Kisel; A. S. Yasukevich; A. N. Shekhovtsov; M. V. Kosmyna; N. V. Kuleshov (Приборы и методы измерений)
The search for new crystalline host materials for the usage in lasers emitting in the eye-safe spectral range of 1.5–1.6 µm is an important task. The aim of this work was to study the growth technique, spectroscopic properties and laser characteristics of new active media – crystals Er3+,Yb3+:Ca2RE2(BO3)4 (RE=Y, Gd).Calcium-yttrium Er3+,Yb3+:Ca3Y2 (BO3)4 (CYB) and calcium-gadolinium Er3+,Yb3+: Ca2 Gd 2(BO3)4  (CGB) oxoborate crystals co-doped with erbium and ytterbium ions were investigated. Polarized absorption and emission cross-section spectra were determined. The lifetimes of 4I11/2 and 4I13/2 energy levels of Er3+ ions were measured and ytterbium-erbium energy transfer efficiencies were estimated. The calculation of the gain cross-section spectra was performed. By using of Er3+,Yb3+: Ca2 RE 2(BO3)4  (RE=Y, Gd) crystals the laser performance was realized, for the first time to the best of our knowledge. The laser characteristics were studied in a quasi-CW (QCW) laser operation.The wide band with a peak at the wavelength of 976 nm is observed in the absorption spectra of both crystals. This peak coincides with the emission wavelength of the pump laser diodes for Yb-doped active media. The maximum value of absorption cross-section was 1.7 × 10–20 cm2 for polarization E // b for both crystals. The lifetimes of the upper laser level 4I13/2 of Er3+ ions were 580 ± 30 μs and 550 ± 30 μs for Er,Yb:CYB and Er,Yb:CGB crystals, respectively. The energy transfer efficiencies from ytterbium to erbium ions for an Er,Yb:CYB and Er,Yb:CGB crystals were 94 % and 96 %, respectively. According to gain spectrum of the Er,Yb:CYB crystal the gain band peak is centered at the wavelength of 1530 nm. The maximum QCW output power was 0.5 W with slope efficiency of 13 % regarding to absorbed pump power for an Er,Yb: CYB crystal. The laser beam parameter M2 did not exceed < 1.5.Based on the obtained results, it can be concluded that these crystals are promising active media for lasers emitting in the spectral range of 1.5–1.6 μm for the usage in laser rangefinder and laser-induced breakdown spectroscopy systems, and LIDARs.